Study of Fair Strategy for Merchant Self-Operated Takeaway Delivery Based on Delivery Plan Optimization - Jing Chen; Chengbo Guo; Jiahua Kou; Jiali Du; Shufa Sun; Yanling Guo (Applied Sciences)
With the increasing demand for takeaway delivery, more merchants are developing their takeaway delivery system to manage order fulfillment and enhance the consumer online experience. This study presents a mathematical model for merchant-operated takeaway delivery, using an improved ant colony algorithm integrated with K-means to cluster customer locations and determine optimal routes. We propose two fairness strategies—order quantity and travel distance—to ensure equitable workload distribution among riders. The K-means algorithm is enhanced by reallocating cluster assignments based on the nodes’ distances to all cluster centers. The simulation results demonstrate that the designed algorithm and strategies generate efficient optimal delivery plans for merchants.